1981
DOI: 10.1111/j.1365-2052.1981.tb01537.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphohexose isomerase polymorphism in the domestic cat

Abstract: Genetic variation of the enzyme phosphohexose isomerase (PHI) has been found in the erythrocytes of Australian domestic cats by horizontal starch gel electrophoresis at pH 8.2. Three complex patterns of isoenzymes, designated F, FS and S , were obtained migrating anodally. Limited family studies and the distribution of the three main phenotypes indicated that the polymorphism is controlled by two codominant autosomal alleles, PHF and PHIS. Gene frequencies for PHF and PHF have been calculated as 0.036 and 0.96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In some previous studies (Auer and Bell 1981;O'Brien 1980;O'Brien et al 1980;Weghe et al 1981;Allan et al 1981), the GPI locus was observed to be polymorphic. Hence the results of the present study are in accordance with earlier research.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…In some previous studies (Auer and Bell 1981;O'Brien 1980;O'Brien et al 1980;Weghe et al 1981;Allan et al 1981), the GPI locus was observed to be polymorphic. Hence the results of the present study are in accordance with earlier research.…”
Section: Resultsmentioning
confidence: 85%
“…The erythrocytes were then washed three times with 0.9% saline and hemolyzed by adding an equal volume of distilled water, and the hemolysate was stored at -20°C prior to analysis. Horizontal starch gel electrophoresis was performed in accordance with standard methods (Altunok et al 1999;Auer and Bell 1981;Grunbaum 1981;Harris and Hopkinson 1976;Hirota et al 1995;Manchenko 2003;Weghe et al 1981), with some minor modifications ( Table 2). The enzyme systems studied were carbonic anhydrase 1 (CA 1 ), phosphogluconate dehydrogenase (PGD), superoxide dismutase (SOD), malic enzyme (ME), glucose phosphate isomerase (GPI, PHI, and PGI), esterase D (ESD), and glutamate oxaloacetate transaminase (GOT, AST).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation